Acute Total Occlusion of the Left Circumflex Coronary Artery Presenting with Non-ST-segment Elevation Myocardial Infraction and Normal Electrocardiogram – A Case Report - Sihite, Teddy Arnold; Hendrawansyah, Sindy; Pranata, Raymond (Open Access Macedonian Journal of Medical Sciences, 2021)
Introduction In this case report, we report a patient with non-ST-segment elevation myocardial infarction (NSTEMI), presenting with recurrent chest pain typical of angina, a very high troponin I level despite normal electrocardiogram (ECG). On angiography, it turns out that the patient has acute total occlusion in the left circumflex artery (LCx). Case Report A 56 years-old woman presented to the emergency department with chief complaint of recurrent chest pain typical of angina 20 hours before admission. Vital signs were within normal limit. There were no murmur, additional heart sounds, and no rales or crackles. The ECG showed normal sinus rhythm, and there were no ST-T changes on serial examination. The first and second cardiac enzymes troponin I was high (> 10 mg/L). Chest X-ray examination showed cardiomegaly without signs of lung edema. Patient was diagnosed with high risk NSTEMI, hypertensive heart disease, and diabetes mellitus. Coronary showed an acute total occlusion in the LCx, which is determined as the culprit lesion for the ongoing myocardial infarction. A drug-eluting stent was deployed at the culprit lesion and the coronary flow was TIMI Flow 3. There was non-significant stenosis at the mid-right coronary artery. The echocardiography showed reduced left ventricular systolic function (LVEF 50%) with hypokinetic inferior-septal and inferior-lateral segment base to apical. Post-procedural follow-up was uneventful. Conclusion One of the learning points is that ECG may fail to detect acute total occlusion and rise in troponin level, despite the absence of ST-T changes, warrant urgent invasive strategy.